Pope and the Blounts: Books Formerly at Mapledurham House - Hone, Joseph (Library, 2023)
Abstract This essay reconstructs a collection of books given by Alexander Pope to the Blount family of Mapledurham in Oxfordshire. The collection includes both books that were presented by the author to the Blounts and also books from his personal library that were bequeathed to Martha Blount in his will. In 1951 more than thirty of the most important books in the collection were sold to the firm of William H. Robinson Ltd. and subsequently dispersed. This essay traces those books and provides their present locations in a finding list. Paying close attention to these books reveals the degree to which Pope was interested not only in the printed form of his writings, but also in their broader bibliographical presentation.